An approach with a queue system to the pandemic period study - Ferreira, M. A. M. (Journal of Modern Accounting and Auditing, 2018)
Epidemics still happen, being the annual influenza outbreaks examples of such occurrences. To estimate the epidemic period length is imperative because, in this period, it is necessary to strengthen the health care, through extra availability in human and material resources. So, a huge increase of expenses occurs. As a pandemic is an epidemic with a great population and geographical dissemination, more appropriately this happens with the pandemic period. Mainly using results on the M|G|? queue busy period, it is presented an application of this queue system to the pandemic period’s parameters and distribution function study.